2016
DOI: 10.1177/1079063216672172
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sexual Abuse in Childhood and the Occurrence of Mental Illness in Adulthood: A Matched Case–Control Study in Nigeria

Abstract: This study aimed to examine the relationship between exposure to childhood sexual abuse (CSA) and the occurrence of mental illness in adulthood in Nigeria. An age- and gender-matched case-control study was conducted in the University of Port Harcourt Teaching Hospital, Nigeria, from January to March 2014. Cases were defined as individuals aged 18 to 60 years diagnosed with mental illness while controls were aged 18 to 60 years who did not have mental illness. The study had 304 subjects comprised of 152 case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Central anxiety), and behavioural difficulties (mistrust of others and missing from home) [15,16,17] Such experiences can also leave victims traumatised by unsavoury memories, which can truncate psychosocial development and impede educational careers [13,14].…”
Section: /12mentioning
confidence: 99%
See 2 more Smart Citations
“…Central anxiety), and behavioural difficulties (mistrust of others and missing from home) [15,16,17] Such experiences can also leave victims traumatised by unsavoury memories, which can truncate psychosocial development and impede educational careers [13,14].…”
Section: /12mentioning
confidence: 99%
“…Common forms of CSA reported were unwanted kissing, hugging, inappropriate touch to breasts and genitals, verbal threats, abuse and rape [22,23,27]. In addition, teenagers were forced to look at pornographic pictures, films, videotapes or magazines, to watch perpetrators exposing genitals and masturbating, coerced into full sexual intercourse, or experienced rape and vaginal or anal penetration [16,25,28]. All the studies found that perpetrators were usually men, mostly known to the victims either as relatives, friends or neighbours.…”
Section: Form Of Csa Reportedmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical consequences of such abuse include injuries, unintended pregnancy, and genital infections [ 21 ]. Those who were sexually abused in childhood are more inclined to develop behavioural and psychological problems such as sleep disturbance, social-related difficulties, eating disorders, self-esteem issues, fear and anxiety, depression, and posttraumatic stress disorder [ 21 , 22 , 23 , 24 , 25 ]. Childhood sexual abuse also increases the risk of future abuse, where the victims are more likely to suffer from domestic violence in their adulthood [ 26 ].…”
Section: Introductionmentioning
confidence: 99%